1984
DOI: 10.1002/1097-0142(19840101)53:1<166::aid-cncr2820530129>3.0.co;2-b
|View full text |Cite
|
Sign up to set email alerts
|

The management of primary carcinoma of the fallopian tube. Experience of 40 cases

Abstract: Forty patients with primary tubal cancer were treated at the Middlesex and Mount Vernon Hospitals between 1951 and 1981. Actuarial 5‐year survival was seen in 68% of 10 Stage I cases, 39% of 17 Stage II cases, and 21% of 11 Stage III cases, and this experience is consistent with other reported postwar series. The disease was found to exhibit some similarity to ovarian cancer in terms of its mode of spread and response to radiation and cytotoxic agents. Transcoelomic spread was identified as the major cause of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
11
0
3

Year Published

1986
1986
2006
2006

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(16 citation statements)
references
References 9 publications
2
11
0
3
Order By: Relevance
“…Our results, as fo age, and distribution of stages, are comparable to those o0 other authors (Pfleiderer, 1984;Bohme et al, 1992;Kubista & Kupka, 1977;Jones, 1965;Denham & MacLennan, 1984;McMurray et al, 1986).…”
Section: Discussionmentioning
confidence: 99%
“…Our results, as fo age, and distribution of stages, are comparable to those o0 other authors (Pfleiderer, 1984;Bohme et al, 1992;Kubista & Kupka, 1977;Jones, 1965;Denham & MacLennan, 1984;McMurray et al, 1986).…”
Section: Discussionmentioning
confidence: 99%
“…The reasons for this might have been insufficient radiation doses, low radiosensitivity of the tumours or early spread beyond the irradiated volume. It should be mentioned, however, that in single cases both partial and complete responses to radiotherapy have been reported (7,9). Although few data exist on the use of whole abdominopelvic irradiation, some authors have reported encouraging results (12, 16, 17).…”
Section: Discussionmentioning
confidence: 99%
“…Radiotherapy could possibly be considered either as adjuvant therapy for early-stage patients [2,5,28,45,46,73,85,[93][94][95][96], for stage III residual negative patients, or in the relapse setting. Although radiotherapy has been used traditionally in the past as an adjuvant therapy for PFTC, its role in the era of effective chemotherapy is less well defined and controversial.…”
Section: Radiotherapymentioning
confidence: 99%
“…Embryologically and histologically the tubal epithelium is derived from the same source as the endometrial epithelium. Progestational agents have been used because of the known cyclic response of the normal tube to hormonal changes during the menstrual cycle [5,85,95]. Because no randomized trials exist and nearly all patients treated with progestational agents are also treated with combination chemotherapy, no firm conclusions can be drawn with regard to their usefulness.…”
Section: Hormonotherapymentioning
confidence: 99%
See 1 more Smart Citation